Curriculum Management and Development of Multicultural Values Based Learning on State Madrasah Tsanawiyah 15 Boyolali - Supriyanto Supriyanto; Amrin Amrin (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to analyze curriculum management and learning development based on multicultural values at MTsN 15 Boyolali as an effort to improve and develop the institution. This research uses field research with qualitative case studies at MTsN 15 Boyolali. The data collection method used in-depth interviews and documentation with research subjects namely the Principal, Deputy Head of Curriculum, and several teachers at MTsN 15 Boyolali. Data analysis was carried out using a flow model, namely data reduction, data presentation and data verification. The results showed that curriculum management and learning development based on multicultural values at MTs N 15 Boyolali had been implemented by taking into account three main components, namely: 1) planning, 2) implementation, and 3) evaluation/supervision. although there are still things that need to be addressed and implemented, such as teachers who lack innovation and the literacy power of teachers about multiculturalism is still weak. So that it requires cooperation from all parties through curriculum management, both from foundations, school principals, teachers, and other parties involved. All of this also needs to be supported by proper education.